1997
DOI: 10.3109/02770909709075657
|View full text |Cite
|
Sign up to set email alerts
|

FEF25–75as a Marker of Airway Obstruction in Asthmatic Children During Reduced Mite Exposure at High Altitude

Abstract: Sensitivity of forced expiratory flow between 25% and 75% of the vital capacity (FEF25-75) in detecting airway obstruction was investigated in 14 children with mild-moderate asthma, allergic to house dust mites, while at high altitude (1756 m). Forced vital capacity (FVC), forced expiratory volume in 1 sec (FEV1), FEF25-75, and peak expiratory flow (PEF) were measured every 2 weeks for 12 weeks (total, 84 measurements). The presence or absence of wheezing at the chest auscultation was ascertained before each t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 12 publications
1
25
0
Order By: Relevance
“…Weighted mean difference KOLESAR et al [19] BONER et al [20] BRIMKULOV (1) [22] BRIMKULOV (2) [22] PIACENTINI et al [23] SIMON et al [24] ALLEGRA et al [11] BONER et al (1) [25] BONER et al (2) [25] KOKOV [26] VAN VELZEN et al [12] VALLETTA et al [27] GROOTENDORST et al [28] PERONI et al [29] STRAUB et al [30] HUISMANS et al [ …”
mentioning
confidence: 99%
“…Weighted mean difference KOLESAR et al [19] BONER et al [20] BRIMKULOV (1) [22] BRIMKULOV (2) [22] PIACENTINI et al [23] SIMON et al [24] ALLEGRA et al [11] BONER et al (1) [25] BONER et al (2) [25] KOKOV [26] VAN VELZEN et al [12] VALLETTA et al [27] GROOTENDORST et al [28] PERONI et al [29] STRAUB et al [30] HUISMANS et al [ …”
mentioning
confidence: 99%
“…16 Our findings also suggest that although there was no variation in the forced vital capacity between the two groups, there was a significant drop in the FEF /FVC ratio in the exposed fishermen, indicating obstruction in the lower respiratory tract. [28][29][30] The major limitation of this study was that fuel emissions and particles in the exhaust were not measured. The trawler boats lack the necessary power supply to support the equipment for these measurements and exposed fishermen remain in the deep sea for up to 20 days at a time.…”
Section: Discussionmentioning
confidence: 99%
“…19 Even though guidelines of American thoracic society does not mention about the role of FEF25-75% in the clinical assessment of airway resistance to flow, some of the studies has shown that FEF25-75% is more sensitive indicator of airway resistance in symptomatic asthma than FEV1 in children and adults. [24][25][26][27][28][29] In term of these parameters, current study suggested that the peripheral airway resistance response to exercise is more compromised among responsive asymptomatic smokers. The airway dilatation and thus decrease in airway resistance is a common physiological response to exercise for normal people, but it appears that partial airway obstruction and weak elastic recoil of lungs is evident in smokers which is leading to a subclinical alteration of ventilatory patterns of small or peripheral airways due to active cigarette smoking.…”
Section: 13mentioning
confidence: 98%